Another Breed of “Service” Animals: STARS Study Findings about Pet Ownership and Recovery from Serious Mental Illness - Wisdom, Jennifer P. (2009)
This study elucidates the role of pets in recovery processes among adults with serious mental illness. Data derive from interviews with 177 HMO members with serious mental illness (52.2% women, average age 48.8). Interviews and questionnaires addressed factors affecting recovery processes and included questions about pet ownership. Data were analyzed using a modified grounded theory method to identify the roles pets play in the recovery process. Primary themes indicate pets assist individuals in recovery from serious mental illness by (a) providing empathy and “therapy”; (b) providing connections that can assist in redeveloping social avenues; (c) serving as “family” in the absence of or in addition to human family members; and (d) supporting self-efficacy and strengthening a sense of empowerment. Pets appear to provide more benefits than merely companionship. Participants’ reports of pet-related contributions to their well-being provide impetus to conduct more formal research on the mechanisms by which pets contribute to recovery and to develop pet-based interventions.